Measuring The Level Of Entrepreneurial Orientation Of Administrative Workers In Hotel Establishments "A Field Study On Four And Five Star Hotels In Lattakia (Journal of Hama University, 2020)
The research aims to determine the level of entrepreneurial orientation among the administrative staff in the four and five-star hotels in the city of Latakia, through the following dimensions: taking risks, creativity and initiative.The researcher relied on the descriptive analytical method based on describing the phenomenon, analyzing it, interpreting the information obtained, and using it to reach generalizations and inferences that include the community in question.The research community includes all the administrative employees in the four and five-star hotel Establishments in the city of Lattakia. As for the research sample, it is a random, accessible sample of (150) workers and administrative workers, where the questionnaire was distributed to the research tool, and (133) questionnaires were retrieved, with a response rate It reached (88.67%).The results showed that the level of entrepreneurial orientation among the administrative staff in the hotel Establishments under